Hubungan Usia Dan Paritas Dengan Kejadian Kekurangan Energi Kronis Pada Ibu Hamil Di Puskesmas Rangkasbitung Tahun 2022 - Rita Ariesta; Kharanita Putri Andini; Puja Wati (Jurnal Obstretika Scientia, 2023)
Nutrition has a major contribution to the life cycle, one of the nutritional problems is malnutrition, both macro and micro nutrients that are manifested in the status of chronic energy deficiency (CHD). SEZ can cause premature LBW babies, stunting and other complications. The indicator of early detection of SEZ is by measuring LiLA (Upper Arm Circumference). The prevalence of SEZ in pregnant women in Indonesia based on Riskesdas data in 2018 was 17.3% and in Southeast Sulawesi it was 28.0%. this type of analytical obsevational research using case control design. the number of samples in this study were 62 pregnant women from 70 populations and a fixed sample of 70 pregnant women was taken. Sampling using total sampling technique according to inclusion criteria, analyzed using Univariate Analysis and Bivariate Analysis with Chi Square statistical test. The results of the study in each variable p value <0.05. The conclusion is that there is a relationship between age and parity to the SEZ of pregnant women at the Rangkasbitung Health Center in 2022. Suggestions to prospective or pregnant women should be pregnancy planning at reproductive age which is 20 years to 35 years and mothers should know the nutritional needs during pregnancy planning and pregnancy period in order to achieve a healthy pregnancy and minimal risk of complications.